Efeitos de um programa de estimulação da consciência fonológica em crianças de educação infantil no ambiente escolar - Brites , Luciana Mota Dias (2021)
Brazil, in the PISA evaluations which had occurred from 2000 to 2018, showed up at one of the worst places in the ranking of reading. Among several factors that contribute to the result, the fact that scientific evidence has been little used for reading education in the country stands out. In this regard, in conjunction with the National Policy of Literacy, implemented in 2019, this research aims to evaluate the effects of a stimulation program of phonological awareness in pre-school children, in the school environment, to investigate the possibility of improving the phonological awareness. This research had four stages: a) choice of a phonological awareness program, b) student evaluation, c) implementation by teachers in class and d) immediate reassessment. The choice of the intervention program was made based on the verification, in several research, that phonological awareness is a predictor of improvement in abilities of reading and writing, besides being a facilitator of the literacy process. It had been chosen a recently program, developed by the same research group as this dissertation. 68 children from the last year of pre-school had been evaluated. To evaluate the performance of the students who participated in this research, the following tests were used: Pre-Alphabetization Skills and Knowledge Test (Teste de Habilidades e Conhecimento Pré-Alfabetização – THCP) and the Phonological Awareness Test by Oral Production (Prova de Consciência Fonológica por Produção Oral – PCFO), in the first and second evaluations. Children were divided into two groups: experimental (n = 38) and control (n = 28). The experimental group received the classroom activities offered by the teachers, working on phonological awareness abilities, while the control group maintained school activities normally. All the stages happened in the school, during the class period, with the authorization of the direction, the teacher and the children parents. Analyses had been conducted to compare the performances of the groups in the tasks, to measure to what extent phonological awareness stimulation can improve the performance in phonological awareness tasks. In conclusion, with regard to the abilities with rhyme, onset and phonemes, there was no difference in testing after the application of the stimulation program, however, with respect to syllabic abilities, the positive impact was observed. The research demonstrated that the stimulation program can be implemented by teachers and that it had demonstrated effects in the experimental group.